Impact of mind-body interventions in older adults with mild cognitive impairment: a systematic review. (4th February 2019) - Farhang, Maryam; Miranda-Castillo, Claudia; Rubio, Miriam; Furtado, Guilherme
ABSTRACT: Background: Mind-body interventions have been associated with a range of positive outcomes in older adults with mild cognitive impairment (MCI). The aim of the present study was to review the impact of different non-pharmacological programs based on mind-body intervention for older adults with MCI. Methods: A comprehensive search method as required by the Cochrane Collaboration has been performed through the following databases: Google Scholar, Science Direct, PubMed, PsycINFO, MEDLINE, EMBASE, CINHAL, Cochrane, Ebsco. We included the studies that evaluated the impact of mind-body interventions such as mindfulness or meditation, yoga, Tai Chi and Qigong on cognitive function and everyday functionality of non-hospitalized adults aged 55 years or over with MCI. Results: Nine studies met the inclusion criteria. Results indicated that mind-body interventions improved cognitive function, everyday activities functioning, and mindfulness, as well as resulting in a moderate reduction in fall risk, depression and stress and lower risk of dementia at one year. Conclusion: Several mind-body interventions focused broadly on mindfulness, yoga and Tai Chi training have been studied. This review shows that mind-body interventions improved cognitive function and everyday activities functioning, memory, resilience and mindfulness in older adults with MCI. However, the conclusions faced limitations, such as small sample size, heterogeneity of outcome measures, lack of an active control group and absence of long-term follow up. Further high-quality evidence is needed in order to determine whether mind-body interventions are cost-effective for improving cognitive decline in older adults with MCI and for delaying the rapid progression from MCI to Alzheimer or other types of dementia.